A disaggregated analysis of productivity and growth for Pakistan’s large scale manufacturing sector - Kamal, Fauzia (International Food Policy Research Institute, 2015)
This research study is thus designed to compute total factor productivity (TFP) growth for Pakistan’s large scale manufacturing (LSM) sector for each five year period from 1970-71 to 2005-06. It covers LSM activity according to the 2 digit Pakistan Standard Industrial Classification (PSIC) 2007, which is comparable with the 3 digit PSIC 19701. The ‘Two Deflator Growth Accounting Framework’ (TDM) introduced by Harberger (1991) is employed in the study to compute the sources of LSM growth, along with the ‘Sunrise-Sunset Approach’ for determining the concentration pattern of TFP. Previous studies on productivity in Pakistan used aggregated data to examine the role productivity has played in economic performance. Even though aggregate productivity is a good measure of the overall efficiency and effectiveness of the economy, substantial information about the distribution of productivity across sectors of the economy is lost. An attempt is thus instigated hereto fill the gap of research on the issue of productivity measurement at the disaggregated level.